The use of complex fertilizers in seed production of winter wheat varieties - N. G. Chertkova; T. I. Firsova; Yu. G. Skvortsova; G. A. Filenko; R. O. Ryabov (Зерновое хозяйство России, 2021)
The current paper has presented the results of the estimation of productivity of the winter wheat varieties ‘Krasa Dona’, ‘Polina’ and ‘Yubiley Dona’ when using liquid complex fertilizers ‘Strada N + Mono Sulfur (S)’, ‘Strada P + Mono Sulfur (S)’ and ‘Diform Silicon-potassium’. The treatment of winter wheat plants was carried out in the form of foliar top-dressings in the stages of tillering and stem extension. The study was carried out on the basis of the FSBSI “Agri- cultural Research Center “Donskoy” in 2019-2020. The trials were laid in the crop rotation of the laboratory for primary seed production and seed study. The purpose was to study the effect of liquid complex fertilizers on the productivity of the studied winter wheat varieties. When using fertilizers for all varieties, there was a tendency to an increase in the density of the productive stand on 18-61 pcs/m2 in comparison with the control. The variety ‘Krasa Dona’ showed the best indicators of the traits ‘number of grains per head’, ‘grain weight per head’ and ‘1000 grain weight’ being fertilized with ‘Strada N + S’ (43 pcs., 2.19 g and 45.7 g) and ‘Diform Silicon-potassium’ (46 pcs., 2.30 g and 46.5 g). The variety ‘Polina’ showed good results after being treated with ‘Strada P + S’ (48 pcs., 2.30 g and 42.1 g) and ‘Diform Silicon-potassium’ (51 pcs., 2.43 g and 42.4 g). The variety ‘Yubiley Dona’ showed the greatest increase of the trait ‘number of grains’ with the fertilizer ‘Diform Silicon-potassium’. The trait ‘1000 grains weight’ had an increase of 2.3 g, and ‘grain weight per head’ was 0.29 g. The treatment with fertilizers did not affect the trait ‘plant height’. The highest productivity of the variety ‘Krasa Dona’ was obtained when being fertilized with ‘Strada N + S’ (9.4 t / ha) and ‘Diforma Silicon-potassium’ (9.5 t/ha); the productivity of the variety ‘Polina’ increased after ‘Strada P + S’ (8.8 t/ha) and ‘Diform Silicon-potassium’ (9.1 t/ha), and the productivity of the variety ‘Yubiley Dona’ increased after ‘Diform Silicon-potassium’ (8.9 t/ha). The maximum economic effect (19080 rubles/ha) with 9.5 t/ha of productivity was obtained from the variety ‘Krasa Dona’ after the treatment with the fertilizer ‘Diform Silicon-potassium’. The experimental results have shown that the use of complex fertilizers has a positive effect on the productivity of winter wheat plants.